A Mendelian randomization study of the effect of serum 25-hydroxyvitamin D levels on autoimmune thyroid disease - Yu, Yunfeng; Yang, Xinyu; Wu, Jingyi; Shangguan, Xueli; Bai, Siyang; Yu, Rong (Frontiers in Immunology, 2024)
Objective: The influence of vitamin D on autoimmune thyroid disease (AITD) remains a subject of ongoing debate. This study employs Mendelian randomization (MR) to investigate the causal correlations of serum 25-hydroxyvitamin D (25[OH]D) levels with autoimmune thyroiditis (AIT), autoimmune hyperthyroidism (AIH), and Graves disease (GD). Methods: Data on single nucleotide polymorphisms related to serum 25(OH)D levels, AIT, AIH, and GD were sourced from UK Biobank and FinnGen. Inverse variance weighted, MR-Egger, and weighted median were employed to test the exposure-outcome causal relationship. Assessments of horizontal pleiotropy, heterogeneity, and stability were performed using the MR-Egger intercept, Cochran's Q test, and leave-one-out sensitivity analysis, respectively. Results: The results of MR analysis showed increased serum 25(OH)D levels was associated with a reduced risk of AIT (OR 0.499, 95% CI 0.289 to 0.860, p = 0.012) but not causal associated with AIH (OR 0.935, 95% CI 0.695 to 1.256, p = 0.654) and GD (OR 0.813, 95% CI 0.635 to 1.040, p = 0.100). Intercept analysis showed no horizontal pleiotropy (p > 0.05), and Cochran's Q test showed no heterogeneity (p > 0.05). Sensitivity analysis suggested that these results were robust. Conclusions: An increased serum 25(OH)D level is associated with AIT risk reduction but unrelated to AIH and GD. This finding suggests that vitamin D supplementation can be valuable for preventing and treating AIT.